Ciprofloxacin-Ioaded Gelatin Microspheres Impregnated Collagen Scaffold for Augmentation of Infected Soft Tissue - Kirubanandan, S. (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: The development of bioactive scaffold to regenerate/augment the connective tissue in infected dermal wounds is still challenging in the field of regenerative medicine and tissue engineering. This is why protein based biomaterial scaffolds that mimic extracellular matrix and acts as the template for the regeneration of dermis and epidermis at the wound site are widely adopted for wound regeneration and soft tissue augmentation. Collagen, the most prominent biomaterials mostly enhance wound healing and maturation of collagen fibers by providing a scaffold for the better rapid transition to tissue with mature, aligned collagen fibers at the wound site. However, in the case of infected wound, wound pathogens secrete enzymes such as bacterial gelatinase and collagenase degrade collagen scaffold as collagen itself is protein. So that, it is necessary to incorporate the antimicrobial agents into the collagen scaffold which can deliver the drugs in a controlled manner by encapsulation of drugs into the vehicles and could be developed to control and eradicate the wound pathogens and supports regeneration faster. Methods: The wound care system which contains a porous collagen scaffold impregnated with ciprofloxacin-loaded gelatin microspheres and has a capable of delivering the ciprofloxacin in a controlled manner at the wound site is developed. The degradation of gelatin microspheres by enzymes secreted by wound pathogens in the wound site ensures drug release at the wound site, and collagen scaffold also supports skin regeneration. The morphological studies of microspheres and microsphere-impregnated collagen are evaluated with scanning electron microscopy. Results and Discussion: The encapsulation efficiency of the drug in gelatin microspheres is 78.6%. In vitro drug release profile confirms that 27% of drug burst released within 5 h followed by controlled release up to 2 days. In vitro antimicrobial evaluation of the scaffold showed the significant zone of inhibition against pseudomonas pathogens. In vivo study of the wound care system showed that gelatin microspheres impregnated in collagen scaffold heal full thickness wound in 12 days, whereas antibiotic incorporated collagen sponge and plain collagen sponge heals in 16 and 20 days, respectively. The wound closure in the animals and histological analysis of granulation tissue confirmed that epidermis and dermis regenerated at the wound site. Conclusion: This investigation suggests that the incorporation of ciprofloxacin-loaded gelatin microspheres impregnated porous collagen scaffold bestows sustained release of ciprofloxacin when gelatin degrades in the infected wound environment, thereby formulating an effective wound care system.